Mitigating acceptance and resistance in the fatwas on the ruling of learning English - Alharbi Ahlam; Bahammam Lubna; Almansour Tahani (Psychology of Language and Communication)
The current study investigated fatwa discourse to reveal the attitudes and rulings of scholars towards English. In doing so, English and Arabic fatwas were analyzed employing modality. It was found that deontic auxiliary modals and similarly functioning markers were utilized to represent acceptance through median value modals to express obligation, for example, “should,” often followed by a justification, and low value modals to express permissibility, for example, “may.” Modality is also used to show resistance through a median value modal, such as “should” and “can.” The manipulation and power of such discourse are evident in the use of modality markers, including auxiliary, semi-auxiliary, and conditional modals. They function on the opposite poles of rulings, permissible and impermissible, to hedge permission and cast hesitation or uncertainty; yet, they show a lack of commitment on the part of the scholars to their fatwa, thus mitigating acceptance and resistance.